2014
DOI: 10.1371/journal.pone.0107659
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a High-Concentrate Corn Straw Diet Induced Epigenetic Alterations in the Mammary Tissue of Dairy Cows

Abstract: PurposeThe objective of this study was to investigate the effects of feeding a high-concentrate corn straw (HCS) diet (65% concentrate+35% corn straw) on the epigenetic changes in the mammary tissue of dairy cows in comparison with a low-concentrate corn straw (LCS) diet (46% concentrate+54% corn straw) and with a low-concentrate mixed forage (LMF) diet (46% concentrate+54% mixed forage).Experimental DesignMultiparous mid-lactation Chinese Holstein cows were fed one of these three diets for 6 weeks, at which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…As a matter of fact, low ruminal pH values led to the lysis of gram-negative bacteria which released LPS into the blood circulation [31, 35]. Consistent with previous studies in dairy cows and feedlot, our results presented higher concentrations of LPS in the peripheral plasma (860 EU/mL) and ruminal fluid (79040 EU/mL) of cows fed a high concentrate die trelative to the peripheral plasma of the LC group [14, 36]. Moreover, we also found that high concentrate diet feeding increased the plasma concentrations of pro-inflammatory cytokines (IL-1β, TNF-α and IL-6).…”
Section: Discussionsupporting
confidence: 90%
“…As a matter of fact, low ruminal pH values led to the lysis of gram-negative bacteria which released LPS into the blood circulation [31, 35]. Consistent with previous studies in dairy cows and feedlot, our results presented higher concentrations of LPS in the peripheral plasma (860 EU/mL) and ruminal fluid (79040 EU/mL) of cows fed a high concentrate die trelative to the peripheral plasma of the LC group [14, 36]. Moreover, we also found that high concentrate diet feeding increased the plasma concentrations of pro-inflammatory cytokines (IL-1β, TNF-α and IL-6).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, overproduction of pro-in ammatory cytokines activated the apoptosis pathway and induced mammary cell apoptosis in lactating cows [32] . Increased amounts of LPS induced by SARA also affect the milk fat and milk protein by enhancing the methylation of genes relevant to fat synthesis and inhibiting the expression of methylation of genes associated with protein synthesis [33,34] . We found that the level of LPS in rumen uid, jugular vein, lacteal vein, milk, and mammary gland all increased in SARA cows, and the content of LPS was higher in mammary gland and milk than in the jugular vein and lacteal vein.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to the milk protein concentration, the differences between the cows that were infused LPS compared with the cows that were infused PLA were longer pronounced in SARA-LPS cows compared with CON-LPS. A possible reason might be that SARA-cows were already subjected to LPS, which might have been translocated from the gastrointestinal tract to the mammary gland (Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The SARA has been associated with the initiation of a chain of metabolic and microbial alterations and dysbiosis in the rumen (Khafipour et al, 2009;Steele et al, 2011), which are implicated in multiple metabolic health disorders in dairy cows. For example, research has shown that cows experiencing SARA are more susceptible to laminitis (Nocek, 1997), metabolic disturbances and inflammation (Plaizier et al, 2008;Zebeli et al, 2011), milk fat depression syndrome (Zebeli and Ametaj, 2009;Dong et al, 2014), liver abscesses and displaced abomasum, and that these cows suffer often from off-feed and ketosis (Kleen et al, 2003;Plaizier et al, 2008;Zebeli et al, 2015). Thus, cows experiencing SARA might be more susceptible to external infectious stimuli such as those occurring during acute mastitis challenge compared with cows that did not experience SARA conditions.…”
Section: Introductionmentioning
confidence: 99%